(untitled) (Zoological Records and Reviews, 2025)
Traditional and local ecological knowledge (TLK) – the cumulative body of knowledge, practices, and beliefs about the relationships between living beings and their environment that has evolved by adaptive processes and been handed down through generations – holds substantial untapped potential for faunal conservation, particularly in extending temporal baselines for species distribution and abundance, detecting cryptic or range-restricted species, and informing culturally appropriate conservation interventions in landscapes where human livelihoods are intertwined with biodiversity. This review synthesises evidence from 172 primary studies (2000-2025) examining the integration of TLK into European and global faunal conservation programmes. We evaluate six integration modalities – historical baseline extension, species occurrence verification, threat identification, management co-design, monitoring co-implementation, and governance participation – across 42 case studies from European pastoral, coastal, and forest landscapes. TLK-based historical baseline extension increases documented species observation windows by a mean 48.4 +- 18.4 years beyond scientific survey records, with highest extensions for large mammals (mean 64.4 years) and coastal fish (mean 72.4 years). TLK verification of modelled species distributions corrected false absence predictions for 28.4% of cells in European large mammal range maps. Community co-designed monitoring programmes show 42% higher volunteer retention than researcher-designed programmes in paired comparisons. Key barriers – epistemic validation challenges, intellectual property concerns, power asymmetries between knowledge holders and research institutions, and absence of TLK integration standards in EU conservation policy frameworks – are analysed alongside practical co-production frameworks. Guidelines for ethical and scientifically rigorous TLK integration in European faunal conservation are presented.